Novel Technique for Management of Axillary Hidradenitis Suppurativa Using Setons - Sepehr Seyed Lajevardi; Jayantha Abeysinghe (Case Reports in Surgery)
Management of hidradenitis suppurativa (HS) of the axilla which is nonresponding to conservative management presents a significant therapeutic challenge. Most surgical treatment options are associated with significant morbidities and prolonged hospital stay. We present a technique of management of HS using setons which is simple and allows the ongoing treatment to be done on an outpatient basis. Given the fact that HS is a chronic relapsing condition each recurrence may again be managed using this technique. This will allow the patients to manage their recurrences with minimal impact on their activities of daily living.